2007
DOI: 10.1039/b707890k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the ozone processing of an unsaturated organic monolayer as a model of an aerosol surface

Abstract: It has been suggested that an organic aerosol containing unsaturated organic compounds at the surface would likely be processed by atmospheric ozone. The ozonolysis of oleic acid gives rise to the formation of products having shorter chain lengths than the starting molecule, and are consequently more water soluble than oleic acid. Hence, the exposure of a monolayer of oleic acid to ozone should lead to a decrease in surface activity at the air-water interface. A model system is used for real-time measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 44 publications
10
54
5
Order By: Relevance
“…The surface reaction rate coefficient k SLR,X,Y = 6 × 10 −12 cm 2 s −1 was adopted from Pfrang et al (2009). Note that this value is an order of magnitude lower than reported value by other studies (Gonzalez-Labrada et al, 2007;King et al, 2009). Bulk diffusion coefficients were adopted from earlier studies (D b,X = 10 −5 cm 2 s −1 , D b,Y = 10 −10 cm 2 s −1 ) (Smith et al, 2002(Smith et al, , 2003, and the parameters of reversible adsorption were adjusted to match the experimental data of oleic acid decay (α s,0,X = 4.2 × 10 −4 and τ d,X = 0.01 s).…”
Section: Model Application: Oxidation Of Oleic Acid By Ozonecontrasting
confidence: 40%
“…The surface reaction rate coefficient k SLR,X,Y = 6 × 10 −12 cm 2 s −1 was adopted from Pfrang et al (2009). Note that this value is an order of magnitude lower than reported value by other studies (Gonzalez-Labrada et al, 2007;King et al, 2009). Bulk diffusion coefficients were adopted from earlier studies (D b,X = 10 −5 cm 2 s −1 , D b,Y = 10 −10 cm 2 s −1 ) (Smith et al, 2002(Smith et al, , 2003, and the parameters of reversible adsorption were adjusted to match the experimental data of oleic acid decay (α s,0,X = 4.2 × 10 −4 and τ d,X = 0.01 s).…”
Section: Model Application: Oxidation Of Oleic Acid By Ozonecontrasting
confidence: 40%
“…However, the rather slow reactions and the similar time constant values indicate that both for the reaction of DPPC and the natural nanolayer the oxidation of the saturated alkyl chains dominates the overall reaction. In comparison, for layers of unsaturated oleic acid, Voss et al (2007) and González-Labrada et al (2007) observed three orders of magnitude faster oxidation processes. Another interesting finding in our preliminary experiments was a surface layer renewal observed for the natural samples, i.e., the SFG signal reappeared overnight.…”
Section: Assessmentmentioning
confidence: 99%
“…5). 42 From a much more fundamental perspective, studies employing self-assembled monolayers (SAMs) as model surfaces have provided detailed insight into the dynamics of gas-surface collisions involving ozone. Specifically, dynamic properties including energy transfer and thermal accommodation coefficients, as well as reaction probability of a single surface-bound functional group, have been revealed using SAMs.…”
Section: à4mentioning
confidence: 99%
“…In the gas phase, O 3 initiates reactions with vinyl-containing organics and polycyclic aromatics via addition across double bonds to form an unstable primary ozonide, which triggers a series of subsequent reactions. [42][43][44] Analogous chemistry may occur on surfaces; [45][46][47] however, scientists are only beginning to decipher how surface structure and functionality affect ozone accommodation, diffusion, and reaction pathways. A quintessential result for these processes is the reactive uptake coefficient: the probability that a gas-phase molecule that collides with the surface will react with the surface.…”
Section: O 3 Reactions With Organic Surfacesmentioning
confidence: 99%